The Cherubic Hymn in The Romanian Choral Creation - Dumitriu George (Sciendo, 2019)
The Cherubic Hymn (gr.) o heroubikos ymnos) was introduced in the Byzantine Liturgy in the 5th century, by a decree of Emperor Justin the 2nd, issued in 574. The document stated the replacement of an old psalm, once sang during the offering of bread and wine gifts at the altar by the church-goers (ofertorium), with the new hymn. The replacement of the ofertoriumului ritual with the one of Presentation of the Euharistic Gifts (the Great Exodus) and the introduction of associated memorials, determined the fragmentation of the hymn in two different parts. Initially sang monodically, the introduction of the art of chorale in the Orthodox Church determined the development of this liturgical singing in two parts with a different musical nature, based on the principle of contrast: Cherubic, in large tempo (Adagio) and That we may receive the King in moderate tempo (Moderato). The first induces an atmosphere of mystical chastity, leads to introversion, and the second is a glory hymn, imposing and majestic. Literary, The Cherubic consists of the following three sentences, which determined the subsequent form of homonym choral creations,